2013
DOI: 10.5006/0848
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Behavior of Metals Used in Drinking Water Distribution Systems: A Rotating Cylinder Electrode's Study

Abstract: The corrosion behavior of electrolytic copper (>99.5% purity [UNS C11000]), carbon steel (AISI/SAE 1016 [(UNS G10160]), and Type 304 (UNS S30400) stainless steel in neutral tap water was examined by potentiodynamic polarization and electrochemical impedance spectroscopy (EIS) using a rotating cylinder electrode (RCE). The instantaneous corrosion rates determined from polarization curves were 0.2, 15, and 140 μm y−1 for stainless steel, copper, and carbon steel, respectively. These values were found to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…2 was given Nyquist (a) and Bode (b) curves for the corrosion behavior of P355 Cs in 1.0 M HCl with and without various doses of BOD after 30 min of immersion. Impedance spectra showed one time constant related to a single capacitive semi-circles, which indicated that the corrosion procedure was mostly controlled by charge transfer [32][33][34][35][36][37][38][39]. The obtained curves are very similar to each other, indicating that the mechanism of corrosion is not different after appending of BOD [40].…”
Section: Resultsmentioning
confidence: 89%
“…2 was given Nyquist (a) and Bode (b) curves for the corrosion behavior of P355 Cs in 1.0 M HCl with and without various doses of BOD after 30 min of immersion. Impedance spectra showed one time constant related to a single capacitive semi-circles, which indicated that the corrosion procedure was mostly controlled by charge transfer [32][33][34][35][36][37][38][39]. The obtained curves are very similar to each other, indicating that the mechanism of corrosion is not different after appending of BOD [40].…”
Section: Resultsmentioning
confidence: 89%
“…The Bode curves for the ZrN, ZrN+1Ag, and ZrN+2Ag coatings show the formation of two-time constants related to the defects in the coating, providing a direct diffusion path for the corrosive media [3] and to the double-layer capacitance [3,43]. Some authors have reported that the presence of two-time constants is typical for porous coatings [3,[43][44][45]. Finally, at 1 h, the impedance module diagram (Figure 7a) showed better performance of all the samples compared to the 316L stainless steel.…”
Section: Corrosion Resistance Of the Coatingsmentioning
confidence: 95%
“…EIS had attained tremendous increase in popularity and dominated the research methods since 2002, when EIS surpassed the research methods of CV and MS. Further, the EIS, which was a mature and well-known technique, had been widely used to analyze the characterization of electrode processes and corrosion performance. During the related researches on electrochemical technology for water and wastewater treatment, EIS mainly applied in the field of corrosion (Liu et al 2003;Rios et al 2013), coatings (Deflorian et al 1994;Deflorian and Fedrizzi 1999), and fuel cells (Yi and Van Nguyen 1999;Lin and Van Nguyen 2005) since 1990s. In addition, EIS, which had been shown to be a powerful and useful tool in different scientific areas, was adopted to investigate the hotspot research on microbial fuel cells (MFCs) (He and Mansfeld 2009;Hosseini and Ahadzadeh 2012).…”
Section: Hot Issuesmentioning
confidence: 99%